(untitled) (Teacher’s World: Journal of Education and Research, 2023)
The department of Educational Psychology and Guidance (EPG) has been serving as a key research, education, and training provider from the very inception of the Institute of Education and Research (IER). The department of EPG contributed to policy formulation for child[1]friendly education through advocating, developing, and adopting innovative practices through research and building capacity through education and training. The study begins by looking at the research landscape of educational psychology in Bangladesh. The study analyses trends of psychological research in education in the last six decades. It also investigates how EPG contributes to imparting the cross-cutting knowledge of educational psychology and developing a skilled workforce over time. Further, it examines how EPG graduates contribute to the field of education in practice. Based on this analysis of research and practices in Bangladesh, some future directions are to be put forward about how the Department of Educational Psychology and Guidance of IER will play a vital role in enhancing the quality of teaching-learning in educational practices in Bangladesh. Vol. 48 (University of Dhaka Centennial Special Issue), June 2022 p.51-69